Syariat Islam Pada Dinasti di Asia Telaah Kritis Tipologi Mujtahid dan Geneologi Intelektual - Hasnul Arifin Melayu (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2014)
Implementation of Islamic law in Aceh is inseparable from its historical context in the history of Islam. Struggle of ideas between religion and state, the influence of the power system and outside the Islamic tradition and social conditions into one format forming Islamic law itself. In addition, the existence of a mujtahid in the struggle also gives an important role. This article will explore specifically about the existence of a mujtahid and their intellectual genealogy in dynasty in Asia, especially the Ottoman and Mughal. This study aims to describe the trip codification of Islamic law in some Muslim region. By doing so, there is the exposure of the expected phases of the codification of Islamic law that can be used as input in the process of implementation of Islamic law in Aceh. Kata kunci: syariat Islam, tipologi, geneologi mujitahid